Subcutaneous emphysema: an indirect sign of anastomotic leak in cecal volvulus - Hoe, Vee Chuan; Kong, Shu Ning; Gilbert, Peh Voon Yeow; Razi, Muhammad Amirrul Nizam; Sibin, Rohamini; Hayati, Firdaus (Faculty of Medicine Universitas Indonesia, 2025)
Cecal volvulus (CV) is a rare cause of intestinal obstruction. A 22-year-old man with cerebral palsy presented with intestinal obstruction symptoms for 2 days. Abdominal computed tomography (CT) revealed a severely dilated cecum, confirmed as CV, during exploratory laparotomy. A right hemicolectomy with primary anastomosis was performed due to an unhealthy cecum. However, his postoperative recovery was stormy as he developed right flank subcutaneous emphysema, but the surgical drain was empty. Follow-up CT showed no extravasation of oral contrast from the lumen, but a relaparotomy noticed a small leak at the posterolateral aspect of the anastomosis, which was reinforced. He recovered well and was discharged 5 days after the relaparotomy. In conclusion, despite being uncommon, subcutaneous emphysema can become an indirect sign of an anastomotic leak even in a negative CT scan.